Analysis of Ganjar Pranowo and Ridwan Kamil’s digital campaign on Twitter - Pranata, Yengki; Hadmar, Ahmad Muhardin; Suswanta, Suswanta (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
Digital campaigns are becoming a trend in influencing public opinion and expanding the reach of political messages. This research aims to analyze the effectiveness of the digital campaign strategy carried out by Ganjar Pranowo and Ridwan Kamil via the Twitter platform. The method used is qualitative research with a Qualitative Data Analysis Software (QDAS) approach via Nvivo 12 Plus. Data was collected using the N-Capture tool via the official Twitter accounts @ganjarpranowo and @ridwankamil during the period July 2022 to June 2023. The accounts @ganjarpranowo and @ridwankamil were chosen as research objects because they are both public figures who have great influence on social media. The analysis is carried out based on five main indicators: popularity, activity, responsiveness, visibility and interaction. The research results show that Ridwan Kamil is more effective in using Twitter as a digital campaign medium. The @ridwankamil account has more than 5.5 million followers, much more than the @ganjarpranowo account which has 3.3 million followers. Ridwan Kamil was also more active in using hashtags, such as #jabarjuara which was used 768 times, while Ganjar Pranowo only used the hashtag #lapakganjar 19 times. However, Ganjar Pranowo shows a higher level of activity with a higher number of tweets and a higher proportion of retweets. Both accounts show almost the same number of mentions on the @jokowi account, reflecting equal involvement in national issues. In conclusion, the @ridwankamil account is more effective than @ganjarpranowo in conducting digital campaigns via Twitter.